1982
DOI: 10.1136/bmj.284.6323.1159-a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cimetidine on portal hypertension in cirrhotic patients.

Abstract: The dangers of inducing diuresis in patients with pulmonary oedema and normal pulmonary wedge pressures have recently been described." We report a complementary case of acute right heart failure due to right ventricular infarction complicated by hypovolaemia. In this, right ventricular output may provide an insufficient preload for the left ventricle, and there is the apparent paradox of an overloaded right ventricle and an inadequately primed "hypovolaemic" left ventricle. Failure to recognise this may lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Alternatively, the different effects could be due to different protein binding, antipyrine being much less extensively bound (46) (53). In patients with more advanced liver disease, propranolol has not been effective (54). This could be due to increased hepatic vascular resistance (55) and/or reduced sensitivity to norepinephrine in the splanchnic vascular bed maintaining high flow against an unchanged hepatic resistance (56).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the different effects could be due to different protein binding, antipyrine being much less extensively bound (46) (53). In patients with more advanced liver disease, propranolol has not been effective (54). This could be due to increased hepatic vascular resistance (55) and/or reduced sensitivity to norepinephrine in the splanchnic vascular bed maintaining high flow against an unchanged hepatic resistance (56).…”
Section: Resultsmentioning
confidence: 99%
“…Antihistamines. Although histamine has been implicated as a mediator of portal hypertension (66) and early reports erroneously assumed that H,-blockers reduced hepatic perfusion (194), it has been shown convincingly that H,-blockers affect neither portal pressure (195,196) nor hepatic perfusion (196)(197)(198). A placebocontrolled trial documented that chronic H,-blockade was unable to prevent repeat bleeding from esophageal varices (199).…”
Section: Angiotensin-converting Enzyme (Ace) Inhibitorsmentioning
confidence: 99%
“…However, gastric pH, and oesophageal reflux have not been shown to be important in the pathogenesis, and a controlled trial of cimetidine in the prophylaxis of variceal haemorrhage demonstrated no improvement (59). Cimetidine's effect on liver blood flow and portal pressure has subsequently been studied by several groups who have reported a variable effect on liver blood flow and no effect on cWHVP (60). At present therefore we do not have any data to support the use of long-term cimetidine or other H,-receptor antagonist in the treatment of portal hypertension and varices (61-63), or in acute variceal haemorrhage, though cimetidine has been shown to be effective in prevention of haemorrhagic gastritis in patients with fulminant hepatitis (64).…”
Section: Prevention Of Recurrent Bleedingmentioning
confidence: 99%